Multi-phase cooling of Early Cretaceous granites on the Jiaodong Peninsula, East China: Evidence from 40Ar/39Ar and (U-Th)/He thermochronology. (July 2018) - Wu, Lin; Monié, Patrick; Wang, Fei; Lin, Wei; Ji, Wenbin; Yang, Liekun
Graphical abstract: Highlights: Biotite Ar-Ar age of 117 Ma and zircon (U-Th)/He age of 93 Ma were obtained for two granites. The two granites have identical cooling history with three rapid cooing phases. Extension, Yanshan Movement, and Cenozoic rifting can explain the rapid cooling phases. Abstract: The Jiaodong Peninsula at the southeastern periphery of the North China Craton (NCC) has undergone complex changes since the Mesozoic. A striking feature of the NCC is the widespread distribution of Late Mesozoic magmatic rocks, predominantly characterized by granitic intrusions. These igneous plutons are economically important due to their polymetallic mineralization and significant as geodynamic tracers of the regional tectonic evolution. Two representative Early Cretaceous granites (the Yashan and Yuangezhuang plutons) on the Jiaodong Peninsula were selected for multiple-thermochronometer studies to constrain a complete thermal history from their emplacement to near-surface conditions. We obtained biotite 40 Ar/ 39 Ar ages of two granites on the new generation Argus VI noble gas mass spectrometer. Two biotites registered identical 40 Ar/ 39 Ar plateau ages of ∼117 Ma, which are consistent within the error with their zircon U-Pb ages. This suggested that the two granites were emplaced at the same time and cooled rapidly to about 300 °C. The single crystal zircon (U-Th)/He (ZHe) dating for the two samples gave weighted mean ages of 93.5 ± 4.5 Ma and 93.3 ± 5.0 Ma. Combined with previously published geochronological data and the thermal inversion of the zircon low temperature thermochronological data, three phases of rapid cooling were identified for the two studied plutons: (1) the Early Cretaceous (117–110 Ma); (2) the Late Cretaceous (100–90 Ma); and (3) the Early Tertiary (65–50 Ma). The Early Cretaceous phase of cooling occurred in a regional extensional regime on the NCC characterized by various extensional structures. The Late Cretaceous cooling is consistent with the third episode of the "Yanshan Movement", which caused a regional basin inversion event on the NCC. In comparison to the first two phases of rapid cooling, the Early Tertiary cooling was more gradual. This phase corresponded to a widely developed Eocene rift on the NCC and the reactivation of major boundary faults, such as the giant Tan-Lu Fault Zone and the Taihangshan Fault.